Malay Magic Being an introduction to the Folklore and Popular Religion of the Malay Peninsula - William Skeat, Walter (MBRAS Reprints, 2005)
This classic account of traditional Malay beliefs was first published in 1900 and reprinted by the Malaysian Branch of the Royal Asiatic Society in 2005. It is now re-issued as a searchable open access e-book.